Contextual effects on the vote in Germany: A multilevel analysis - Jan Pickery (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
This paper addresses the old topic of contextual effects on voting behaviour. Current multilevel analysis techniques provide a powerful tool to (re-)examine such regional influ-ences on individual voting decisions. We apply multilevel analysis to German electoral data. Our results prove evidence of two contextual effects. The unemployment level of the district has a positive effect on SPD support, which confirms the local equivalent of the economic vote model. Furthermore the global strength of a party in a district has a positive effect on the individual decision to support that party. This is a confirmation of what has been labelled as breakage. Both effects demonstrate the continuing impact of the locality on individual vote preferences in Germany. – – Diese Arbeit befasst sich mit dem alten Thema der Kontexteffekte beim Wahlverhalten. Neue Techniken der Multi-Level-Analyse bieten ein mächtiges Instrument, mit dem regionale Einflüsse auf Wahlentscheidungen (neu) untersucht werden können. Die Multi-Level-Analyse wird auf deutsche Wahldaten angewendet und weist zwei Kontexteffekte nach. Die Arbeitslosenquote des Wahlkreises hat einen positiven Effekt auf die Unterstützung der SPD, was dem regionalen Äquivalent des Modells des economic voting entspricht. Außerdem wirkt sich die allgemeine Stärke einer Partei in einem Kreis positiv auf die individuelle Entscheidung aus, diese Partei zu unterstützen. Dieses zweite Ergebnis bestätigt die Annahme, die als Breakage bezeichnet wird. Beide Effekte zeigen, dass individuelle Wahlentscheidungen in Deutschland weiterhin regionalen Einflüssen unterliegen.
Keywords: 300